Logistics Modeling of Multimodal Transport of Cargo from Origin to Destination: An Empirical Case of Chemical Cargo from Java to Both Java and Sumatera Points - Gurning, Raja Oloan Saut; Gunarta, I Ketut; Widiastuti, Hera; Andrian, Felix; Herijanto, Wahju; Prastyanto, Catur Arif; Kartika, Anak Agung Gde; Wantoro, Dimas (IPTEK Journal of Proceedings Series, 2018)
To build an efficient transportation system product, possible alternatives paths and modes of transportation for all types of products to be marketed and distributed are signifcant requirements need to be mapped by logistics operator. It becomes more complex due to each product type has its own characteristics and market objectives, thus this is requiring the design of transport schemes that can accommodate those needs in addition to be able to meet its sales target of cargo producers, both in terms of selling volume and revenue. Selection of the appropriate transport scheme is one of the key to achieve efficiency in companies’ operation. Therefore, this study explores the comprehensive transportation process including the route and its capacity, vehicle, cargo volume and the time so that the objectives to transport the cargo is achieved. At the result, the logistics model using networking analysis by Excel and ARENA that has been aplied in this study may be used as optimization method of transporting and distributing cargoes including able to provide recommendations pattern / scheme of transport and logistics effectively and efficiently from Java to both various points in Java and Sumatera